2004
DOI: 10.1136/bjsm.2003.007518
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory resistive loading improves cycling capacity: a placebo controlled trial

Abstract: Background: Respiratory muscle training has been shown to improve both its strength and endurance. The effect of these improvements on whole-body exercise performance remains controversial. Objective: To assess the effect of a 10 week inspiratory resistive loading (IRL) intervention on respiratory muscle performance and whole-body exercise endurance. Methods: Fifteen apparently healthy subjects (10 men, 5 women) were randomly allocated to one of three groups. One group underwent IRL set at 80% of maximum inspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
73
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 25 publications
11
73
2
Order By: Relevance
“…Using IMT, one study observed an increase in inspiratory muscle strength of ~41% in healthy subjects (Enright et al, 2006). Other studies using healthy subjects found smaller increases in inspiratory muscle strength of ~7-17% (Downey et al, 2007;Gething et al, 2004;Holm et al, 2004;Witt et al, 2007). The difference in these studies appears to be the intensity at which the IMT was performed, varying from 50-80%, with the largest increases observed at 80% (Downey et al, 2007;Enright et al, 2006;Gething et al, 2004;Witt et al, 2007).…”
Section: Respiratory Muscle Strengthmentioning
confidence: 89%
See 1 more Smart Citation
“…Using IMT, one study observed an increase in inspiratory muscle strength of ~41% in healthy subjects (Enright et al, 2006). Other studies using healthy subjects found smaller increases in inspiratory muscle strength of ~7-17% (Downey et al, 2007;Gething et al, 2004;Holm et al, 2004;Witt et al, 2007). The difference in these studies appears to be the intensity at which the IMT was performed, varying from 50-80%, with the largest increases observed at 80% (Downey et al, 2007;Enright et al, 2006;Gething et al, 2004;Witt et al, 2007).…”
Section: Respiratory Muscle Strengthmentioning
confidence: 89%
“…Other studies using healthy subjects found smaller increases in inspiratory muscle strength of ~7-17% (Downey et al, 2007;Gething et al, 2004;Holm et al, 2004;Witt et al, 2007). The difference in these studies appears to be the intensity at which the IMT was performed, varying from 50-80%, with the largest increases observed at 80% (Downey et al, 2007;Enright et al, 2006;Gething et al, 2004;Witt et al, 2007). Effects observed with high intensity IMT are consistent with those observed in this study, suggesting that the greater inspiratory muscle strength we observed with HIT compared to ET, was due to greater demand placed on the respiratory muscle with HIT.…”
Section: Respiratory Muscle Strengthmentioning
confidence: 89%
“…However, this seems doubtful since the RT2 inspiratory muscle trainer used in the present study, which utilizes inspiratory flow resistive loading and the TIRE protocol, has previously been shown to improve both the strength and endurance of the inspiratory muscles. Improved cycling capacity in healthy subjects (Gething et al 2003;Gething et al 2004b) has been reported. Increased strength and endurance of the inspiratory muscles, enhanced lung volume (VC), increased diaphragm thickness and greater exercise capacity in healthy subjects (Enright et al 2006) has also been shown with similar equipment and protocols.…”
Section: Influence Of Imt On Pulmonary and Respiratory Muscle Functionmentioning
confidence: 99%
“…The device used was the RT2 trainer and associated software (DeVilbiss Sunrise Medical Ltd, Wollaston, UK). The RT2 training device is a pressure manometer with a 2mm leak, which utilises an infra-red link to a computer containing the software of the "Test of Incremental Respiratory Endurance" (TIRE) regimen, as previously described (Chatham et al 1999;Chatham et al 2004;Enright et al 2004;Gething et al 2004a;Gething et al 2004b). The 2mm leak provides a set resistance to inspiratory flow.…”
Section: Inspiratory Muscle Training Protocolmentioning
confidence: 99%
“…However, there is no consensus about an optimal protocol to induce and assess the fatigability of the inspiratory muscles [3]. Although the ergogenic effect of respiratory muscle training (rMT) remains controversial [4][5][6], several recent well-controlled studies have shown that threshold inspiratory muscle training (IMT) [7][8][9][10], as well as voluntary normocapnic hyperpnoea training [10,11] can improve exercise performance in healthy subjects. In general, the functional capacity of the healthy human respiratory system, including the lung, chest wall, and neural control systems, exceeds the demands placed upon it during heavy exercise.…”
Section: Introductionmentioning
confidence: 99%